Heat shock proteins: A dual carrier-adjuvant for an anti-drug vaccine against heroin - Hwang, Candy S.; Ellis, Beverly; Zhou, Bin; Janda, Kim D. (Bioorganic & Medicinal Chemistry, 2019)
Heroin is a highly abused opioid that has reached epidemic status within the United States. Yet, existing therapies to treat addiction are inadequate and frequently result into rates of high recidivism. Vaccination against heroin offers a promising alternative therapeutic option but requires further development to enhance the vaccine’s performance. Hsp70 is a conserved protein with known immunomodulatory properties and is considered an excellent immunodominant antigen. Within an antidrug vaccine context, we envisioned Hsp70 as a potential dual carrier-adjuvant, wherein immunogenicity would be increased by co-localization of adjuvant and antigenic drug hapten. Recombinant Mycobacterium tuberculosis Hsp70 was appended with heroin haptens and the resulting immunoconjugate granted anti-heroin antibody production and blunted heroin-induced antinociception. Moreover, Hsp70 as a carrier protein surpassed our benchmark Her-KLH cocktail through antibody-mediated blockade of 6-acetylmorphine, the main mediator of heroin’s psychoactivity. The work presents a new avenue for exploration in the use of hapten-Hsp70 conjugates to elicit anti-drug immune responses.
11 citations (Crossref) [2023-10-31]
Keywords: Adjuvant; Carrier protein; Heat shock protein; Heroin; Immunotherapy; Opioids; Vaccines; dept.che; peer-reviewed